Breeding method of selenium-rich ducks - LAN MING (2017)
The invention belongs to the technical field of livestock breeding and particularly relates to a breeding method of selenium-rich ducks. The breeding method of the selenium-rich ducks comprises steps as follows: (1) field selection; (2) building of duck sheds; (3) feeding of the ducks; (4) stocking of the ducks. By means of the breeding method, growth and development of the ducks can be promoted, the disease resistance of the ducks is improved, and the survival rate of the ducks is greatly increased; deposition of fat in the ducks can be prevented, and the content of vitamins in the ducks is increased, so that meat of the ducks becomes more delicious and more nutritious . The selenium-rich ducks produced with the method have high selenium content, and the selenium content of different parts is about 2 times that of ordinary ducks. 本发明属于畜牧养殖技术领域，具体涉及种富硒鸭的养殖方法。所述富硒鸭的养殖方法，包含如下步骤:(1)园地选择(2)鸭舍的建造(3)鸭子的喂养(4)鸭子的放养。通过本发明的养殖方法，不仅能促进鸭子的生长发育、提高鸭子的抗病能力，使鸭子的成活率大大提高，而且可以降低鸭子体内脂肪的沉积，使鸭子体内的维生素含量得到增加，从而让鸭子的肉质变得更加美味和营养；本发明方法生产